(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the outcome of patients treated with external fixation for fractures of shaft of humerus. Study Design: Descriptive / case series study Place and Duration of Study: This study was conducted at the Department of Orthopaedic Surgery Quaid-e-Azam Medical College /B.V. Hospital Bahawalpur from May 2015 to October 2017. Materials and Methods: The variable noted were age, sex, presenting complaint, duration of fracture, associated injuries and radiological finding before definitive management. The operative findings, site of fracture, postoperative course (pain, healing & mobility), Complications (swelling, neurovascular damage, infection, delayed and nonunion), Patients satisfaction, Clinical and radiological maturation of bone at fracture site were recorded. Results: Total of 65 patients treated in study time. Fifty one were male and 14 were female. Mean age was 37 years (range 20 years to 40 years). The mean follow-up period was 16 weeks. (SD±4.7).There were 6 superficial infections treated successfully using oral antibiotics and no case was reported fornon-union. Conclusion: External fixationis good method of treatment for humeral shaft fractures.This technique although is surgical demanding but leads to decrease soft tissue trauma.